KINERJA PERTUMBUHAN DAN DINAMIKA KUALITAS AIR PADA BUDIDAYA ANGGUR LAUT (Caulerpa sp.) DENGAN NAUNGAN BERBEDA - Riris Yuli Valentine; I Nyoman Sudiarsa; Sartika Tangguda; Dimas Rizky Hariyadi (University of Prof. Dr. Hazairin, SH, 2021)
Seagrapes (Caulerpa sp.) is one of the aquatic plants which tends to grow slowly according to the environmental conditions where sea grapes live. This study aims to determine the growth performance of sea grapes given different shelters. The method used in this study was three treatments, each treatment was repeated three times, with differences in the shade (P1 = paranet), (P2 = without roof), and (P3 = coconut leaves). Data analysis used a non-factorial completely randomized design (CRD). The results of this study are at absolute weights (P1 =1163.3 ± 260a g), (P2 = 210 ± 79.3b g), (P3 = 922 ± 199.5a g), absolute length (P1 = 5.75 ± 1.74a cm), (P2 = 0.59 ± 0 , 07b cm), (P3 = 4.82 ± 0.22a cm), daily growth rate (4.40 ± 0.1a %), (3.76 ± 0.09b %), (4.29 ± 0.09a) and the number of ramuli (P1 = 56.2 ± 21.3a), (P2 = 19.5 ± 2.3b), (P3 = 46.3 ± 3.1a). The conclusion of this study each parameter (absolute weight, absolute length and number of ramuli) has a significant difference.